Comparative static structural assessment of an energy-efficient prototype vehicle chassis using finite element analysis: AISI 1020 steel vs. 6061-T6 aluminum - Muhammad Fadil Andira; Wanda Afnison; Waskito Waskito; Delima Yanti Sari (Journal of Engineering Researcher and Lecturer, 2025)
This study evaluates the static structural performance of a Prototype-class energy-efficient vehicle chassis for the Indonesian Kontes Mobil Hemat Energi (KMHE; Energy-Efficient Car Competition) by comparing two material options, AISI 1020 carbon steel and Al 6061-T6, under a consistent load representation. Three-dimensional chassis models were developed in SolidWorks and assessed using static finite element analysis (FEA). The loading scenario included gravitational body force and two concentrated static loads representing operational conditions: 700 N applied at the driver seat region and 300 N applied at the engine mounting area. A curvature-based meshing strategy was adopted, with element sizes ranging from 1.6 to 8 mm, resulting in approximately 1,700,093 nodes to capture geometric details in joints and curved members. The AISI 1020 chassis produced a maximum von Mises stress of 278.6 MPa concentrated near the engine mounting joint, a maximum total deformation of 2.1 mm in the roll-bar region, and a minimum factor of safety of 1.3. In contrast, the Al 6061-T6 chassis exhibited a lower peak stress of 61 MPa at the rear wheel mounting region, a higher deformation of 3.4 mm at the roll bar, and a factor of safety of 4.5. The findings confirm a trade-off between stiffness and safety margin: steel offers higher stiffness but an insufficient safety margin, while aluminium significantly improves the static safety margin with increased deformation. These results provide design guidance for reinforcing critical regions and enhancing the robustness of competition-ready chassis.